Charging cable for water surface suspension type reflective ship and manufacturing method of charging cable
By using base materials such as TPU, polycaprolactone, cellulose nanocrystals and nanoaluminum hydroxide, the tensile performance of the outer sheath of the cable is enhanced and phosphor coated on the cable, the shore power cable is solved by using base materials such as TPU, polycaprolactone, cellulose nanocrystals and nanoaluminum hydroxide. The problem of damage caused by hanging has improved the power supply reliability and night visibility of the shore power system.
Patent Information
- Application Number
- CN202411453700.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The tensile resistance of the existing shore power cables is limited, and it is easy to be damaged or broken due to hooking during ship docking, affecting the power supply reliability of the shore power system.
The base material consisting of TPU, polycaprolactone, cellulose nanocrystals and nanoaluminum hydroxide is used to enhance the tensile strength of the outer sheath of the cable, and the outer sheath is coated with phosphor on the surface to improve night and rainy days. Recognition, reduce the risk of hooking.
Significantly improve the tensile strength of the outer sheath of the cable, reduce the risk of breakage due to hooking, ensure the stable operation of the shore power system, and improve the visibility of the cable at night and rainy days through fluorescence, avoiding the past Hooks of ships and machinery.
Smart Images

Figure CN119252538A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of cable technology, and more specifically, to a surface-suspended reflective ship charging cable and a manufacturing method thereof. Background Art
[0002] As countries around the world pay more attention to environmental pollution, international regulations and standards for exhaust gas pollution generated by ships while moored in ports are becoming increasingly stringent. In this context, the ship shore power system can supply power to ships through the power supply system installed on the shore and the power receiving system installed on the ship, so it does not generate exhaust gas pollution during the ship's mooring process, and can well meet the requirements of relevant regulations and standards. The promotion of this technology is conducive to achieving energy conservation and emission reduction and promoting green shipping, and has become a major development trend in the shipping industry.
[0003] At present, there are many ways to connect shore power systems, including barge connection, dock mobile connection, container connection, shipboard matching connection, etc. Regardless of which connection method is used, shore power cables are ultimately required. With the maturity of technology, the specifications and weight of shore power cables are gradually increasing, and the operating conditions they face are becoming increasingly complex.
[0004] In view of the above-mentioned related technologies, the inventor believes that during the use of shore power cables, they often need to withstand the tension from ships, drums, and winches. In special cases, they also need to withstand the tension generated by hooking with passing ships, reefs, shells or other seabed obstacles. The outer sheath of the cable is often the most direct target of the tension, and the tensile performance of the outer sheath of the cables currently on the market is limited. When the ship is docked at night, it is easy to get hooked due to insufficient visibility, causing damage to the cable or even breaking it, which will affect the power supply reliability of the shore power system. Summary of the invention
[0005] The tensile strength of the outer sheath of the cables currently on the market is limited. When the ship is docked at night, the cable is easily damaged or even broken due to the hooking of the ship, which can easily affect the power supply reliability of the shore power system. In order to improve this defect, the present application provides a surface-suspended reflective ship charging cable and a manufacturing method thereof.
[0006] In a first aspect, the present application provides a surface-suspended reflective ship charging cable, which adopts the following technical solution: A water-surface suspended reflective ship charging cable comprises a core and an outer sheath, wherein the outer sheath is coated on the surface of the core, the surface of the outer sheath is coated with an antifouling coating, and the outer sheath comprises the following components: 1.8-2.0wt% of an additive, 3.0-3.2wt% of a pigment, 5-8wt% of a filler, 5-8wt% of a fluorescent powder, 5-10wt% of a flame retardant, and 1.0-1.2wt% of a dispersant, and the balance is supplemented to 100wt% by a base material, and the components of the base material include TPU, polycaprolactone, cellulose nanocrystals, and nano-aluminum hydroxide.
[0007] By adopting the above technical scheme, the present application defines that the components of the base material include TPU, polycaprolactone, cellulose nanocrystals and nano aluminum hydroxide. The main chain of TPU is composed of a soft segment and a hard segment, the hard segment mainly provides mechanical strength, and the soft segment gives TPU a certain deformation ability. Polycaprolactone can be used as a plasticizer to improve the flexibility of TPU, and is easy to disperse in TPU. The polycaprolactone dispersed in the base material can absorb and disperse the tensile stress of the outer sheath together with the soft segment in TPU, reducing the stress concentration in the local area of the outer sheath. Both cellulose nanocrystals and nano aluminum hydroxide have a large number of hydroxyl groups on their surfaces, which can form a strong hydrogen bond with TPU through the hydroxyl groups, and a part of the hydroxyl groups can also react with the isocyanate groups in the TPU raw material, which not only promotes the close combination of cellulose nanocrystals and nano aluminum hydroxide with TPU, but also plays a plasticizing role, thereby synergistically improving the flexibility of TPU with polycaprolactone. By applying the base material of the present application, the tensile strength of the cable outer sheath can be fully improved, so that the cable outer sheath is not easy to break under tension when being hooked by a ship, which helps to maintain the stable operation of the shore power system. In addition, the addition of fluorescent powder also provides a certain degree of recognition for the cable, which can make the cable more conspicuous at night and on rainy days, helping to avoid the hooking of the cable by passing ships and port machinery and equipment, and reducing the risk of the cable breaking under tension.
[0008] Preferably, the wire core includes an inner core, a foam isolation sleeve and a braided layer; the inner core includes multiple wires and multiple foam filling bodies; the wires include a twisted conductor and an insulating sleeve, the twisted conductor is formed by twisting multiple soft copper wires around an aramid core material, and the insulating sleeve is coated on the surface of the twisted conductor; the foam filling body is filled in the gap between two adjacent wires; the foam isolation sleeve is coated on the outside of the inner core, the braided layer is coated on the surface of the foam isolation sleeve, and the outer sheath is coated on the surface of the braided layer.
[0009] By adopting the above technical solution, the present application further defines the internal structure of the wire core. In the wire core of the present application, since the stranded conductor uses aramid core material as the central component, the high tensile strength of the aramid core material can be fully utilized, which helps to reduce the frequency of core breakage during the use of the cable. The design of the foam filler and the foam isolation layer reduces the deadweight of the cable, which helps to reduce the creep generated by the cable during immersion in water.
[0010] Preferably, the cellulose nanocrystals are prepared according to the following method: The microcrystalline cellulose and sulfuric acid solution are mixed, stirred and heated to obtain a cellulose acid hydrolysate; ice water is added to the cellulose acid hydrolysate to terminate the reaction, and the mixture is allowed to stand for stratification, and after removing the supernatant, the suspension at the bottom is centrifuged and washed to obtain a centrifuge; the centrifuge is dialyzed to a neutral pH to obtain a dialysate, and the dialysate is ultrasonically dispersed and freeze-dried to obtain cellulose nanocrystals.
[0011] By adopting the above technical solution, the present application uses sulfuric acid to acid-hydrolyze microcrystalline cellulose, destroying the amorphous region of the microcrystalline cellulose and obtaining cellulose nanocrystals with a large number of hydroxyl groups on the surface.
[0012] Preferably, the nano aluminum hydroxide is prepared according to the following method: The ammonia solution is continuously added to the saturated alum solution, and the pH value is continuously stirred and detected. When the pH reaches neutral, the addition of ammonia solution is stopped, and then centrifugation is performed. After the supernatant is discarded, water is added and stirred, and then centrifugation is performed again. After the supernatant is discarded, aluminum hydroxide colloid is obtained; the aluminum hydroxide colloid is mixed with polyether, stirred, sheared and dispersed, and then the mixture is distilled and dehydrated to obtain nano aluminum hydroxide.
[0013] By adopting the above technical scheme, the present application uses alum as an aluminum source, converts aluminum ions into aluminum hydroxide by adding ammonia water, and then extracts the aluminum hydroxide through subsequent steps to obtain nano aluminum hydroxide with a large number of hydroxyl groups on the surface.
[0014] Preferably, the base material further comprises cesium lead bromide, which is mixed with the polyurethane prepolymer solution during the preparation of the base material.
[0015] By adopting the above technical scheme, cesium lead bromide has a certain fluorescent effect. By adding cesium lead bromide to the base material, the fluorescent effect of cesium lead bromide can be used to form a synergistic combination with the fluorescent powder, which can make the cable more conspicuous at night and on rainy days, help avoid the cable being hooked by passing ships and port machinery and equipment, and reduce the risk of the cable being broken by tension.
[0016] Preferably, the base material is prepared according to the following method: A polyurethane prepolymer solution is prepared, cellulose nanocrystals, nano aluminum hydroxide and a chain extender are added to the polyurethane prepolymer solution in sequence, and the solution is cured by heat preservation after stirring. The cured product is melt-blended with cesium lead bromide and polycaprolactone to obtain a base material.
[0017] By adopting the above technical solution, the present application optimizes the preparation method of the base material. By adding cellulose nanocrystals and nano-aluminum hydroxide into the prepolymer, a strong chemical bond can be formed between TPU and the two, which helps to fully enhance the tensile properties of the outer sheath.
[0018] Preferably, the filler comprises barium sulfate.
[0019] By adopting the above technical solution, the present application preferably uses barium sulfate as the filler component of the outer sheath, and the dispersant in the outer sheath component can make the barium sulfate evenly dispersed. The barium sulfate and the base material can move and deform together under the action of external force, thereby increasing the effective cross-sectional area that bears external loads and helping to enhance the tensile strength of the outer sheath.
[0020] Preferably, the filler further comprises glass micro-beads and ceramic micro-beads, and the average particle size of the glass micro-beads and ceramic micro-beads is 2-5 μm.
[0021] By adopting the above technical solution, the present application preferably uses glass microbeads and ceramic microbeads with an average particle size of 2-5 μm as fillers. The ceramic microbeads and glass microbeads have retroreflective function, which can make the incident light return in the opposite direction of the light source, and provide sufficient recognition for the cable at night, which helps to reduce the hooking of the cable by passing ships.
[0022] In a second aspect, the present application provides a method for manufacturing a surface-suspended reflective ship charging cable, which adopts the following technical solution.
[0023] A method for manufacturing a water-surface suspended reflective ship charging cable comprises the following steps: (1) Assembling the wire cores for standby use; preparing the antifouling coating for standby use; mixing the additives, pigments, fillers, fluorescent powders, flame retardants, dispersants and base materials, and obtaining the sheath material after kneading for standby use; (2) co-extruding the wire core and the sheath material to obtain an outer sheath covering the surface of the wire core; (3) A layer of antifouling paint is coated on the surface of the outer sheath, and the antifouling paint is cured into an antifouling coating by static curing to obtain a water-surface-suspended reflective ship charging cable.
[0024] By adopting the above technical scheme, the present application first prepares a wire core, an antifouling coating and a sheath material, then covers the outer sheath made of the sheath material on the surface of the wire core, and then applies an antifouling coating on the surface of the outer sheath to obtain a surface-suspended reflective ship charging cable.
[0025] Preferably, the antifouling coating comprises a modified bentonite, and the modified bentonite is prepared according to the following method: The spice extract is added into ethanol, and then bentonite is added into the ethanol for ultrasonic dispersion to obtain a dispersion liquid, and the dispersion liquid is dried to obtain modified bentonite; the spice extract has the following structure: HO(CH3)2CCH2NHCOCH=CHCH2CH2CH2CH3.
[0026] By adopting the above technical solution, the present application dissolves the spice extract in ethanol and uses bentonite to absorb the spice extract to obtain modified bentonite containing the spice extract. The spice extract can hinder the attachment of barnacle larvae. By using the modified bentonite as a component of the antifouling coating, the number of barnacles adhering to the cable surface can be reduced, which helps to maintain the cleanliness of the cable surface.
[0027] In summary, this application has the following beneficial effects: 1. The present application defines that the components of the base material include TPU, polycaprolactone, cellulose nanocrystals and nano-aluminum hydroxide. By applying the base material of the present application, the tensile strength of the cable outer sheath can be fully improved, so that the cable outer sheath is not prone to tensile fracture when being hooked by a ship, which helps to maintain the stable operation of the shore power system.
[0028] 2. The present application adds fluorescent powder to the outer sheath. The addition of fluorescent powder provides a certain degree of recognition for the cable, making the cable more conspicuous at night and on rainy days, helping to avoid being hooked on the cable by passing ships and port machinery and equipment, and reducing the risk of the cable breaking under tension.
[0029] 3. This application uses bentonite as a carrier and adds a spice extract to the anti-fouling coating on the surface of the outer sheath, which can reduce the number of barnacles adhering to the cable surface and help maintain the cleanliness of the cable surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a cross-sectional schematic diagram of a water-surface-suspended reflective ship charging cable according to an embodiment of the present application.
[0031] Description of reference numerals: 1. Outer sheath; 2. Braided layer; 3. Foam isolation sleeve; 4. Foam filling body; 5. Insulation sleeve; 6. Soft copper wire; 7. Aramid core material. DETAILED DESCRIPTION
[0032] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0033] Preparation example of base material The following is an explanation using Preparation Example 1.
[0034] Preparation Example 1 The cellulose nanocrystals involved in this preparation example were prepared according to the following method: 50 g of microcrystalline cellulose and 750 mL of a 64 wt% sulfuric acid solution were mixed, stirred and heated at 45°C, and a cellulose hydrolysate was obtained after 60 minutes; ice water in an amount ten times the weight of the cellulose hydrolysate was added to the cellulose hydrolysate to terminate the reaction, and the mixture was allowed to stand for stratification, and after removing the supernatant, the suspension at the bottom was centrifuged and washed to obtain a centrifuge; the centrifuge was dialyzed until the pH value was neutral to obtain a dialysate, and the dialysate was ultrasonically dispersed and freeze-dried to obtain cellulose nanocrystals.
[0035] The nano aluminum hydroxide involved in this preparation example was prepared according to the following method: Continuously adding 25 wt % ammonia solution to the saturated alum solution, stirring continuously and detecting the pH value, stopping adding ammonia solution after the pH reaches neutral, then centrifuging, discarding the supernatant, adding water and stirring, then centrifuging again, discarding the supernatant to obtain aluminum hydroxide colloid; mixing aluminum hydroxide colloid with polytetramethyl ether glycol (M n =1000) were mixed in a weight ratio of 1:3, stirred and sheared for dispersion, and then the mixture was distilled and dehydrated under a heating condition of 110° C. in an oil bath to obtain nano aluminum hydroxide.
[0036] This preparation example provides a base material, which is prepared according to the following method: Polytetramethyl ether glycol and diphenylmethane diisocyanate are weighed in a weight ratio of 1:3, the polytetramethyl ether glycol is heated to 115°C, vacuum dewatered at 0.09MPa for 2h, then cooled to 50°C, diphenylmethane diisocyanate and a catalyst are added, the temperature is raised to 80°C, the mixture is reacted in a nitrogen atmosphere for 3h, vacuum degassing is performed for 0.5h, and DMF is added to prepare a polyurethane prepolymer solution with a solid content of 40wt%; cellulose nanocrystals, nano-aluminum hydroxide and a chain extender are added to the polyurethane prepolymer solution in sequence (the weight of the cellulose nanocrystals, nano-aluminum oxide and the chain extender are respectively equivalent to 1%, 2% and 1% of the solid content of the polyurethane prepolymer solution), after stirring for 20min, the mixture is heat-cured at 80°C for 48h, and after standing at 20°C for 5d, the cured product is melt-blended with polycaprolactone in a weight ratio of 15:1 to obtain a base material.
[0037] Preparation Example 2 The difference between this preparation example and preparation example 1 is that in the method for preparing the base material, the cured product is melt-blended with polycaprolactone and cesium lead bromide to obtain the base material, and the weight of cesium lead bromide is equivalent to 2% of the solid content of the polyurethane prepolymer solution.
[0038] Preparation Example of Antifouling Coating Preparation Example 3 is used as an example below.
[0039] Preparation Example 3 In this preparation example, the spice powder is pepper powder with an average particle size of 4.5 μm.
[0040] This preparation example provides an antifouling coating, which is prepared according to the following method: (1) using tetrahydrofuran as solvent and dibutyltin laurate as catalyst, triclosan and isocyanoethyl methacrylate are compounded in a molar ratio of 1:1 and reacted, and after keeping the reaction at 55° C. for 24 hours, the solvent is removed by rotary evaporation at 50° C. to obtain vinyl-modified triclosan, which is then used for later use; (2) vinyl modified triclosan and butyl acrylate are mixed in a molar ratio of 1:5, and then a solvent prepared by ethylene glycol monomethyl ether and xylene in a weight ratio of 1:1 is added to obtain a monomer dispersion having a monomer mass fraction of 25%; after heating the monomer dispersion at 80° C. for 2 hours, n-dodecyl mercaptan is added in an amount of 20% by weight of the monomer, and the reaction is continued at the temperature for 2 hours, and then an initiator AIBN is added in an amount of 4% by weight of the total monomer weight, and the reaction is continued for 2 hours to obtain an antifouling resin; (3) 30 g of antifouling resin, 9 g of rosin, 7 g of xylene, 7 g of ethylene glycol monomethyl ether, 0.3 g of BYK163, 0.3 g of BYK104S, 5 g of mancozeb, 5 g of diuron, 15 g of spice powder, 1 g of zinc oxide, 1 g of barium sulfate, 1 g of iron oxide, 0.5 g of BYK052, 0.35 g of BYK354, and 15 g of bentonite were mixed and ball-milled for 48 h, and then the ball-milled product was added to a solvent prepared by ethylene glycol monomethyl ether and xylene in a weight ratio of 1:1 to obtain an antifouling coating with a solid content of 70%.
[0041] Preparation Example 4 The difference between this preparation example and preparation example 3 is that bentonite is replaced by modified bentonite, and the modified bentonite is prepared according to the following method: The spice extract, ethanol and bentonite are weighed in a weight ratio of 1:50:10, the spice extract is first added to the ethanol, and then the bentonite is added to the ethanol for ultrasonic dispersion to obtain a dispersion, and the dispersion is dried to obtain modified bentonite for later use. In the method, the spice extract has the following structure: HO(CH3)2CCH2NHCOCH=CHCH2CH2CH2CH3. Example
[0042] The following description is given by taking Example 1 as an example.
[0043] Example 1 This embodiment provides a water-surface floating reflective ship charging cable, referring to Figure 1 The water-surface suspended reflective ship charging cable includes a core and an outer sheath 1, the outer sheath 1 is coated on the surface of the core, and the surface of the outer sheath 1 is coated with an antifouling coating. The core includes an inner core, a foam isolation sleeve 3 and a braided layer 2; the inner core includes three wires and three foamed fillers 4; the wire includes a twisted conductor and an insulating sleeve 5, the twisted conductor is formed by 19 soft copper wires 6 twisted around an aramid core material 7, and the aramid core material 7 is formed by 7 aramids with a specification of 1100; the insulating sleeve 5 is coated on the surface of the twisted conductor; the foamed filler 4 is filled in the gap between two adjacent wires; the foam isolation sleeve 3 is coated on the outside of the inner core, the braided layer 2 is coated on the surface of the foam isolation sleeve 3, and the outer sheath 1 is coated on the surface of the braided layer 2.
[0044] In this embodiment, the outer sheath includes the following components: 1.8wt% of additives, 3.0wt% of pigments, 5wt% of fillers, 5wt% of phosphors, 5wt% of flame retardants, and 1.0wt% of dispersants, and the balance is supplemented by the base material to 100wt%. The additives include antioxidants and light stabilizers, and the antioxidant is mixed with BASF 1010, BASF 168, Chemtura 412s, Yinjing antioxidant 300#, and BASF anti-copper agent 1024 in a weight ratio of 5:3:5:3:2; the light stabilizer is mixed with BASF light stabilizer 944 and BASF ultraviolet light absorber 326 in a weight ratio of 1:1. The pigment is carbon black powder (Cabot BP800), the filler is barium sulfate, the phosphor is green silicate phosphor (Interma G 1758), the flame retardant is Zhejiang Xusen XS-FR-8370 nitrogen-phosphorus halogen-free flame retardant, the dispersant is Shandong Sike V172 silane coupling agent, and the base material is prepared according to the method of Preparation Example 1.
[0045] This embodiment provides a method for manufacturing a water-surface-suspended reflective ship charging cable, comprising the following steps: (1) producing and assembling the wire core for standby use; preparing the antifouling coating according to the method of Preparation Example 3 for standby use; mixing the auxiliary agent, pigment, filler, phosphor, flame retardant, dispersant and base material, and obtaining the sheath material after kneading for standby use; (2) co-extruding the wire core and the sheath material to obtain an outer sheath covering the surface of the wire core; (3) Antifouling paint is applied to the surface of the outer sheath, and the antifouling paint is cured into an antifouling coating with a thickness of 300 μm by static curing, thereby obtaining a water-surface floating reflective ship charging cable.
[0046] As shown in Table 1, the main difference between Examples 1-3 is that the raw material ratios of the outer sheath are different.
[0047] Table 1 Ratio of raw materials for outer sheath Example 4 The difference between this embodiment and embodiment 3 is that the base material is prepared according to the method of preparation example 2.
[0048] Example 5 The difference between this embodiment and embodiment 4 is that the filler is composed of barium sulfate, glass microspheres and ceramic microspheres in a weight ratio of 1:2:1, and the average particle size of the glass microspheres and ceramic microspheres is 5 μm.
[0049] Example 6 The difference between this embodiment and embodiment 5 is that the average particle size of the glass microbeads and the ceramic microbeads is 3.5 μm.
[0050] Example 7 The difference between this embodiment and embodiment 5 is that the average particle size of the glass microbeads and the ceramic microbeads is 2 μm.
[0051] Example 8 The difference between this embodiment and embodiment 7 is that the antifouling coating is prepared according to the method of preparation example 4.
[0052] Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the base material is replaced with TPU elastomer (Wanhua Chemical TPU WHT-1195).
[0053] Comparative Example 2 This comparative example is different from Example 1 in that the base material does not include polycaprolactone.
[0054] Comparative Example 3 This comparative example is different from Example 1 in that the base material does not include cellulose nanocrystals.
[0055] Comparative Example 4 The difference between this comparative example and Example 1 is that the components of the base material do not include nano aluminum hydroxide.
[0056] Comparative Example 5 The difference between this comparative example and comparative example 1 is that the surface of the outer sheath is not coated with an antifouling coating.
[0057] Performance testing methods In the following test items, except for Comparative Example 5, all the test samples were provided with an antifouling coating with a thickness of 300 μm.
[0058] 1. Tensile strength test The sheath materials in each embodiment and comparative example were selected as the test object, and the national standard "GB / T 1040.3-2006 Determination of tensile properties of plastics" was referred to, and a 5-type dumbbell specimen was obtained for testing using an adhesive strength tester (QT-6201S). The test speed was 50mm / min, and the test gauge length was 25mm. Three dumbbell specimens were taken from each group of samples for testing, and the average value was taken as the experimental result. Taking the tensile strength measured in comparative example 1 as the benchmark, the ratio between the tensile strength of each embodiment and comparative example and the tensile strength of comparative example 1 was calculated, and the ratio was recorded as the relative tensile strength. The results are shown in Table 2.
[0059] 2. The sheath materials in each embodiment and comparative example were selected as the detection object, and the fluorescence intensity was tested by a fluorescence spectrophotometer (LS-45 / 55, Perkin Elmer, USA). The sample size was a circular film with a diameter of 15 mm and a thickness of 2 mm, which was fixed on the solid sample holder of the spectrometer. The excitation wavelength was set to 513 nm, and the wavelength test range was 450-650 nm.
[0060] Taking the fluorescence intensity measured in Comparative Example 1 as a reference, the ratio between the fluorescence intensity of each embodiment and comparative example and the fluorescence intensity of Comparative Example 1 was calculated, and the ratio was recorded as the relative fluorescence intensity. The results are shown in Table 2.
[0061] 3. Retroreflection coefficient The sheath materials of Examples 5 to 8 were selected as test objects, and the retroreflection coefficient was tested according to the method specified in GB / T 16311-1996. The results are shown in Table 2.
[0062] 4. Adhesion coefficient The cables in the embodiments and comparative examples were selected as the test objects, and a 6 cm long cable was immersed in a container filled with artificial sterile seawater. 100 larvae of reticulated barnacles were added to the container for cultivation. After 120 hours, the number of barnacles adhering to the surface of the cable was counted, and the ratio of the number to the initial number 100 was recorded as the adhesion rate of the sample. Five parallel tests were set for each group of samples, and the average value of the adhesion rates measured by the five parallel tests was rounded off as the final result, and the results are shown in Table 2.
[0063] Table 2 Test results sample Relative tensile strength / % Relative fluorescence intensity / % <![CDATA[Retroreflective coefficient / (mcd / lxm 2 )]]> Adhesion rate / % Example 1 126.8 99.9 / 52 Example 2 127.4 100.4 / 53 Example 3 129.1 101.7 / 50 Example 4 132.6 116.7 / 51 Example 5 132.9 117.6 190 50 Example 6 133.6 119.9 210 52 Example 7 134.8 120.1 240 51 Example 8 134.9 120.0 240 32 Comparative Example 1 100.0 100.0 / 51 Comparative Example 2 104.4 99.8 / 52 Comparative Example 3 111.7 99.9 / 51 Comparative Example 4 109.6 99.8 / 53 Comparative Example 5 126.5 100.0 / 88 Combining Examples 1-3 and Comparative Examples 1-4 and Table 2, it can be seen that the cables of Examples 1-3 have a higher tensile strength, which is because the polycaprolactone dispersed in the base material can absorb and disperse the tensile stress of the outer sheath together with the soft segment in the TPU, reducing the stress concentration in the local area of the outer sheath. At the same time, there are a large number of hydroxyl groups on the surface of cellulose nanocrystals and nano-aluminum hydroxide, which can form a strong hydrogen bond with TPU through the hydroxyl groups, and a part of the hydroxyl groups can also react with the isocyanate groups in the TPU raw material, while promoting the close combination of cellulose nanocrystals and nano-aluminum hydroxide with TPU, it also plays a plasticizing role, thereby synergistically improving the flexibility of TPU with polycaprolactone. When pure TPU is selected as an alternative base material, or when any one of polycaprolactone, cellulose nanocrystals and nano-aluminum hydroxide is missing in the base material, the above synergistic effect is difficult to fully achieve, so the tensile performance of the outer sheath is poor.
[0064] Combining Example 1 and Comparative Example 5 and Table 2, it can be seen that the adhesion rate measured in Example 1 is significantly lower than that in Comparative Example 5, indicating that the present application has sufficiently reduced the adhesion of barnacles on the cable surface by setting an anti-fouling coating.
[0065] Combining Example 3 and Example 4 with Table 2, it can be seen that the cable of Example 4 has a higher fluorescence intensity. This is because cesium lead bromide has a certain fluorescence effect. By adding cesium lead bromide to the base material, the fluorescence effect of cesium lead bromide can be used to cooperate with the phosphor, which can make the cable more conspicuous at night and on rainy days, help avoid the cable being hooked by passing ships and port machinery and equipment, and reduce the risk of the cable being broken by tension.
[0066] Combining Example 4 and Examples 5-7 with Table 2, it can be seen that barium sulfate, glass beads and ceramic beads can all improve the tensile strength of the outer sheath, and the addition of glass beads and ceramic beads can also make the outer sheath have a certain retroreflective effect, which can make the cable more conspicuous at night and on rainy days by forming a combination with the fluorescent powder.
[0067] Combining Example 7 and Example 8 with Table 2, it can be seen that the adhesion rate measured in Example 8 is lower than that in Example 7, indicating that the spice extract introduced with bentonite as a carrier can further reduce the adhesion of barnacles on the cable surface.
[0068] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A charging cable for a water-surface suspended reflective ship, characterized in that: The invention comprises a wire core and an outer sheath (1), wherein the outer sheath is coated on the surface of the wire core, and the surface of the outer sheath is coated with an antifouling coating. The outer sheath comprises the following components: 1.8-2.0wt% of an auxiliary agent, 3.0-3.2wt% of a pigment, 5-8wt% of a filler, 5-8wt% of a fluorescent powder, 5-10wt% of a flame retardant, and 1.0-1.2wt% of a dispersant. The balance is supplemented by a base material to 100wt%. The base material comprises components of TPU, polycaprolactone, cellulose nanocrystals, and nano-aluminum hydroxide.
2. The water-surface-suspended reflective ship charging cable according to claim 1, characterized in that: The wire core comprises an inner core, a foam isolation sleeve (3) and a braided layer (2); the inner core comprises a plurality of wires and a plurality of foamed fillers (4); the wires comprise a twisted conductor and an insulating sleeve (5); the twisted conductor is formed by twisting a plurality of soft copper wires (6) around an aramid core material (7); the insulating sleeve (5) is coated on the surface of the twisted conductor; the foamed filler (4) is filled in the gap between two adjacent wires; the foam isolation sleeve (3) is coated on the outside of the inner core, the braided layer (2) is coated on the surface of the foam isolation sleeve (3), and the outer sheath (1) is coated on the surface of the braided layer (2).
3. The water-surface-suspended reflective ship charging cable according to claim 1, characterized in that: The cellulose nanocrystals are prepared according to the following method: The microcrystalline cellulose and sulfuric acid solution are mixed, stirred and heated to obtain a cellulose acid hydrolysate; ice water is added to the cellulose acid hydrolysate to terminate the reaction, and the mixture is allowed to stand for stratification, and after removing the supernatant, the suspension at the bottom is centrifuged and washed to obtain a centrifuge; the centrifuge is dialyzed to a neutral pH to obtain a dialysate, and the dialysate is ultrasonically dispersed and freeze-dried to obtain cellulose nanocrystals.
4. The water-surface-suspended reflective ship charging cable according to claim 1, characterized in that: The nano aluminum hydroxide is prepared according to the following method: The ammonia solution is continuously added to the saturated alum solution, and the pH value is continuously stirred and detected. When the pH reaches neutral, the addition of ammonia solution is stopped, and then centrifugation is performed. After the supernatant is discarded, water is added and stirred, and then centrifugation is performed again. After the supernatant is discarded, aluminum hydroxide colloid is obtained; the aluminum hydroxide colloid is mixed with polyether, stirred, sheared and dispersed, and then the mixture is distilled and dehydrated to obtain nano aluminum hydroxide.
5. The water-surface-suspended reflective ship charging cable according to claim 4, characterized in that: The components of the base material also include cesium lead bromide, which is mixed with the polyurethane prepolymer solution in the method of preparing the base material.
6. The charging cable for a water-surface-suspended reflective ship according to claim 5, characterized in that: The base material is prepared as follows: A polyurethane prepolymer solution is prepared, cellulose nanocrystals, nano aluminum hydroxide and a chain extender are added to the polyurethane prepolymer solution in sequence, and the solution is heat-insulated and cured after stirring. The cured product is melt-blended with cesium lead bromide and polycaprolactone to obtain a base material.
7. The water-surface-suspended reflective ship charging cable according to claim 1, characterized in that: The filler includes barium sulfate.
8. The charging cable for a water-surface-suspended reflective ship according to claim 7, characterized in that: The filler also includes glass micro beads and ceramic micro beads, and the average particle size of the glass micro beads and ceramic micro beads is 2-5 μm.
9. The method for manufacturing a water-surface-suspended reflective ship charging cable according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Assembling the wire cores and setting them aside; preparing the antifouling coating and setting them aside; mixing the additives, pigments, fillers, fluorescent powders, flame retardants, dispersants and base materials, and obtaining the sheath material after mixing and setting them aside; (2) Co-extruding the wire core and the sheath material to obtain an outer sheath covering the surface of the wire core; (3) A layer of antifouling paint is coated on the surface of the outer sheath, and the antifouling paint is cured into an antifouling coating by static curing, thereby obtaining a water-surface-suspended reflective ship charging cable.
10. The water-surface-suspended reflective ship charging cable according to claim 9, characterized in that: The components of the antifouling coating include modified bentonite, and the modified bentonite is prepared according to the following method: The spice extract is added into ethanol, and then bentonite is added into the ethanol for ultrasonic dispersion to obtain a dispersion liquid, and the dispersion liquid is dried to obtain modified bentonite; the spice extract has the following structure: HO(CH3)2CCH2NHCOCH=CHCH2CH2CH2CH3.
Citation Information
Patent Citations
Preparation method of mesoporous imprinted nanocellulose based carbon nanotube adsorption material
CN110052252A
Cellulose nanocrystal modified polyurethane prepolymer and preparation method thereof
CN116355170A
Novel bio-based thermoplastic polyurethane elastomer composite material and preparation method thereof
CN116790111A
Cellulose nanocrystals - thermoset resin systems, applications thereof and articles made therefrom
US20160002462A1
